Communication as tool for conflict management and conflict resolution (2010)
Communication and conflict are intricately connected as a feature of every human society. Inadequate or poor quality of communication invariably leads to conflict at the individual level and it ultimately leads to social conflicts. However, if adequate attention is paid to communication dynamics in any relationship and in the society, the ultimate result is improvement and development in relationships and in the social environment. This paper examines the intricate web of communication and conflict by looking at the role of perception and stereotypes in the communication process and how it could aggravate social conflict. It analyses how some of the common errors committed in the communication process could lead to misunderstanding, and it makes suggestions on deliberate steps that could be taken to ensure that communication is adopted as a tool to enhance better understanding and quick resolution of conflicts